Age and factors associated with access and time to post-operative adjuvant chemotherapy in colon cancer: a French epidemiological study - Capsec, Jean; Lefebvre, Carole; Chupé, Fabienne; Heitzmann, Patrick; Raveneau, Céline; Dardaine-Giraud, Véronique; Sauger, Carine; Lagasse, Jean-Paul; Kraft, Kevin; Linassier, Claude; Dorval, Etienne (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
Background: Studies have shown the negative prognostic impact of increased time between colectomy and postoperative adjuvant chemotherapy (AC) in colon cancer (CC). Our aim was to investigate the role of age and non-organizational factors on access and time to AC. Methods: All adult patients undergoing surgery for stage II or III CC in the “Région Centre-Val de Loire” in 2013, were selected. Time to AC and socio-demographic factors were collected. Logistic regression modeling was used to identify factors associated with access to AC, and a multivariate analysis performed to identify factors associated with time to AC. Results: Among 404 stage II or III patients who underwent colectomy, 182 (45%; sex ratio 1.5; mean age 67.6 years; range 32–90) received AC. AC patients were younger than those without AC (67.6 vs. 77.9 years) and the difference was even greater for stage III patients (69.0 vs. 82.4). The median time to AC was 48 days, exceeding 42 days in 60% of cases. Living alone, postoperative morbidities, and emergency colectomy were independently associated with increased time to AC. Age and other factors were not associated with delayed AC. Conclusions: Emergency colectomy, postoperative morbidities, and living alone are associated with increased time to AC. Organizational measures to reduce the time to AC are therefore unlikely to have an impact. In contrast, age is not associated with increased time to AC, but to access to AC. Reasons for omitting AC in older patients requires further study.